Situation Report: Romania, 26 April 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. CC Plenum Approves Ceausescu Visit to Africa Relations with France Relations with Yugoslavia Military News Party Membership and Activity Discussed CC Adopts Decision on Data Processing Economic News